The literary life of Cairo : one hundred years in the heart of the city - Mehrez, Samia (American University in Cairo Press, 2011)
Unlike The Literary Atlas of Cairo, which focuses on the literary geopolitics of the cityscape, this companion volume immerses the reader in the complex network of socioeconomic and cultural lives in the city. The seven chapters first introduce the reader to representations of some of Cairo's prominent profiles, both political and cultural, and their impact on the city's literary geography, before presenting a spectrum of readings of the city by its multiethnic, multinational, and multilingual writers across class, gender, and generation. Daunting images of colonial school experiences and star.